The potential role of kelp forests on iodine speciation in coastal seawater. - Jennifer Gonzales; Teresa Tymon; Frithjof C Küpper; Matthew S Edwards; Carl J Carrano (PLoS ONE)
Kelps have a major role in marine and atmospheric iodine cycling in the coastal zone of temperate regions, with potential wide-ranging impacts on ozone destruction in the coastal marine boundary layer. However, little is known about the impact of kelp forests on iodine speciation in coastal sea water. To address this, we examined iodide and iodate concentrations in seawater in and around a giant kelp forest near San Diego, CA, USA, and a nearby site that was not influenced by kelp biology. Our data shows that while both iodide and iodate concentrations remained unchanged during the year at the nearby site, these concentrations changed significantly in and around the kelp forest, and were strongly related to changes in kelp canopy biomass. In particular, iodide reached its highest concentration and iodate reached its lowest concentration during the summer when the kelp canopies were near their maximum, while the opposite pattern was observed during the winter and spring when the kelp canopies were near their minimum. Further, comparisons of these changes with corresponding changes in seawater temperature and wind speed indicated that these relationships were relatively small compared to those with changes in kelp biomass. Together, our data show a strong relationship between kelp biomass and iodine metabolism.